L’estasi della soglia e il Nulla. Intorno a un «Osso» Montaliano - Celada Ballanti, Roberto (Bollettino Filosofico, 2017)
The essay about Eugenio Montale explores, philosophically, a specific lyric poem of Cuttlefish Bones: «Maybe one morning...». On the one hand, – as is well known to Montalian criticism – this is a text that has essential implications on the nihilism’s level, since it suspend phenomenical reality to the void and nothingness, on the other hand it contains a figure of the religious sphere ideally contemporary: the possibility that from that nothing, from that void, the miracle can open up to a revelation which saves and redeems the contingency in some aporetic eternity.